Anxiety disorders, climate change, and the challenges ahead: Introduction to the special issue. (December 2020) - Taylor, Steven
Highlights: Climate change involves extreme weather events and more gradual climatic changes. Anxiety to climate change can be either adaptive or maladaptive. Adaptive anxiety can motivate climate activism. Widescale programs are needed to build individual and community resilience. Widescale programs are needed to treat disorders arising from climatic stressors. Abstract: Climate change involves (1) increases in the prevalence of extreme weather events (e.g., wildfires, floods, hurricanes), (2) more gradual climatic changes (e.g., rising sea levels, desertification), and (3) increased risks of pandemics and other widespread disease outbreaks. Anxiety evoked by the threat of climate change can be either adaptive or maladaptive. Adaptive anxiety can motivate climate activism, such as efforts to reduce one's carbon footprint. Maladaptive anxiety can take the form of anxious passivity, where the person feels anxious but incapable of addressing the problem of climate change, and may take the form of an anxiety disorder triggered or exacerbated by climatic stressors. Such stressors may involve exposure to extreme weather events or may involve exposure to other stressors such as forced migration due to rising sea levels or desertification. Three types of interventions are needed to address the various types of climate-related anxiety: (1) programs that motivate people to overcome anxious passivity and thereby take action to mitigate the effects of climate change, (2) treatment programs that address anxiety associated with exposure to climatic stressors, and (3) programs that build resilience at an individual and community level, to help people better cope with the challenges ahead.